Evidence of Volatility Metals and Metalloids at Environment Conditions - Svetlana B. Bortnikova; Nataliya V. Yurkevich; Sergey S. Volynkin; Aleksander S. Kozlov; Alexey L. Makas (Applied Sciences, 2022)
Tailings represent a significant risk to the environment globally, but very little is known about the composition of the near-surface air. We conducted laboratory experiments to determine the sizes of the particles and the chemical composition of the flow above the mine waste. A condensate of vapor–gas flow was collected in parallel with particle control by an aerosol diffusion spectrometer (ADS). We reveal that there were no aerosol particles bigger than 3 nm in the flow. The collected condensate contained chemical elements, ions of sulfates, chlorides, phosphates, and formates and a wide range of sulfur-, selenium-, and carbon-containing gases. The main findings of the study are the presence of the metals Zn, Cu, Fe, Al, Cd, Ni, and Ba and the metalloids As, Sb, Se, Ag, Co, Ti, and V in the true-gas phase or in the form of particles smaller than 3 nm in the air above the mine tailings. The surprising fact is that the migration of metals and metalloids in a true-gas form or in ultrafine particles (<3 nm) is possible, which opens up a new research direction on the volatile forms of chemical elements in various climatic conditions and their bioavailability and toxicity.